Pengobatan Tradisional Kapuntori di Desa Labone Kecamatan Lasalepa Kabupaten Muna - Boymin; Syahrun; Rahmat Sewa Suraya (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
Kapuntori is an alternative method that is believed by the Muna people as a treatment to achieve one's desires. This treatment spread among the Muna people through a process of inheritance from generation to generation by their ancestors. This research aims to find out the form and function of Kapuntori traditional medicine in the Muna community in Labone Village, Lasalepa District. This is a qualitative descriptive research with data collected through observation and interviews. Data analysis was carried out by listening to interview results, writing interview transcripts, sorting the data, and looking for relationships between functions based on the functionalism theory put forward by Malinowski. The traditional form of Kapuntori treatment carried out by Bhisa in Labone Village, Lasalepa District has a sspecific form, such as the use of water as a medium which has a cooling function and is easily absorbed by the body and is believed to be able to enter between the skin and bones in the body. Thus, a prayer that is blown into the water can be absorbed by the body immediately so that it quickly brings healing. This treatment also uses some leaves of herbal plants, namely Karuku. Kapuntori treatment has a suggestion function that aims to provide influence or views from one party (the shaman) to another party (the patient), as a result, the party being influenced will be moved to follow this influence or view and accept it directly, either consciously or unconsciously. This treatment also intends to hope for healing from Allah SWT through an intermediary of people who can cure diseases (Bhisa).